Estimating natural frequency of pipe with various geometries: improvement of frequency factors - Saari, Noor Fariza; Putra, Azma; Irianto; Dan, Reduan Mat; Zeli, Muhammad Agus; Ramlan, Roszaidi; Abdul Jalil, Nawal Aswan; Herawan, Safarudin (Elsevier, 2024)
Piping system is the main structure in many industrial applications, especially for large industry relating with processing and transporting fluids, such as oil and gas industries. The fluid-induced vibration is often the cause of structural fatigue in pipes and therefore piping vibration need to be closely monitored. In case of high piping vibration, knowledge of the natural frequency of a pipe section is crucial for an engineer to propose the right troubleshoot action, either for a temporary or even for a long-term solution for the piping vibration. Therefore, prediction of the pipe natural frequency using a simple formulae is thus of interest, without dealing with complex numerical simulation using a commercial software which consumes cost and time. In this paper, the vibration mode shapes of various possible geometries of pipes in practice were simulated in ANSYS and the simulated natural frequency is related to a natural frequency of an Euler-Bernoulli beam using a correction factor for each corresponding piping geometry. This paper extends the previous work by allowing the boundary conditions of the pipe ends to be simply supported, in addition to the clamped edges. In this way, the frequency factor charts are presented in the range of possible correction factor values to accommodate the real conditions of pipe arrangement in practical application. An experiment from a case study to verify the proposed method is also presented.